94.8k views
0 votes
Work out the first four terms and the 10th term of the quadratic

sequence with
a T(n) = 2n2 + 4
b T(n) = 3n2-3
c T(n) = -3n2 + 7
d T(n) = 4n? -5

User Yooakim
by
5.3k points

1 Answer

2 votes

Answer:

a. The first four terms and the 10th term are 6, 12, 22, 36, ......., 204

b. The first four terms and the 10th term are 0, 9, 24, 45, ......., 297

c. The first four terms and the 10th term are 4, -5, -20, -41, ......., -293

d. The first four terms and the 10th term are -1, 11, 31, 59, ......., 395

Explanation:

a.

T(n) = 2n² + 4 is the rule of the sequence, where

  • n is the position of the number in the sequence

∴ For the first term, n = 1

→ Substitute n by 1 in the rule above to find T(1)

∵ T(1) = 2(1)² + 4 = 2(1) + 4 = 2 + 4

T(1) = 6

→ For the second term, n = 2

∵ T(2) = 2(2)² + 4 = 2(4) + 4 = 8 + 4

T(2) = 12

→ For the third term, n = 3

∵ T(3) = 2(3)² + 4 = 2(9) + 4 = 18 + 4

T(3) = 22

→ For the fourth term, n = 4

∵ T(4) = 2(4)² + 4 = 2(16) + 4 = 32 + 4

T(4) = 36

→ For the tenth term, n = 10

∵ T(10) = 2(10)² + 4 = 2(100) + 4 = 200 + 4

T(10) = 204

The first four terms and the 10th term are 6, 12, 22, 36, ......., 204

b.

T(n) = 3n² - 3 is the rule of the sequence

→ For the first term, n = 1

∵ T(1) = 3(1)² - 3 = 3(1) - 3 = 3 - 3

T(1) = 0

→ For the second term, n = 2

∵ T(2) = 3(2)² - 3 = 3(4) - 3 = 12 - 3

T(2) = 9

→ For the third term, n = 3

∵ T(3) = 3(3)² - 3 = 3(9) - 3 = 27 - 3

T(3) = 24

→ For the fourth term, n = 4

∵ T(4) = 3(4)² - 3 = 3(16) - 3 = 48 - 3

T(4) = 45

→ For the tenth term, n = 10

∵ T(10) = 3(10)² - 3 = 3(100) - 3 = 300 - 3

T(10) = 297

The first four terms and the 10th term are 0, 9, 24, 45, ......., 297

c.

T(n) = -3n² + 7 is the rule of the sequence

→ For the first term, n = 1

∵ T(1) = -3(1)² + 7 = -3(1) + 7 = -3 + 7

T(1) = 4

→ For the second term, n = 2

∵ T(2) = -3(2)² + 7 = -3(4) + 7 = -12 + 7

T(2) = -5

→ For the third term, n = 3

∵ T(3) = -3(3)² + 7 = -3(9) + 7 = -27 + 7

T(3) = -20

→ For the fourth term, n = 4

∵ T(4) = -3(4)² +7 = -3(16) + 7 = -48 + 7

T(4) = -41

→ For the tenth term, n = 10

∵ T(10) = -3(10)² + 7 = -3(100) + 7 = -300 + 7

T(10) = -293

The first four terms and the 10th term are 4, -5, -20, -41, ......., -293

d.

T(n) = 4n² - 5 is the rule of the sequence

→ For the first term, n = 1

∵ T(1) = 4(1)² - 5 = 4(1) - 5 = 4 - 5

T(1) = -1

→ For the second term, n = 2

∵ T(2) = 4(2)² - 5 = 4(4) - 5 = 16 - 5

T(2) = 11

→ For the third term, n = 3

∵ T(3) = 4(3)² - 5 = 4(9) - 5 = 36 - 5

T(3) = 31

→ For the fourth term, n = 4

∵ T(4) = 4(4)² - 5 = 4(16) - 5 = 64 - 5

T(4) = 59

→ For the tenth term, n = 10

∵ T(10) = 4(10)² - 5 = 4(100) - 5 = 400 - 5

T(10) = 395

The first four terms and the 10th term are -1, 11, 31, 59, ......., 395